Lactation Tetany In A Pony And Its Therapeutic Management - A.Kishorekumar; P. Pothiappan; C.S. Arunaman (The Indian Veterinary Journal, 2024)
A two-year-old recently foaled pony was presented to the Large Animal Medicine Unit of Madras Veterinary Teaching Hospital with a history of reduced appetite and inability to walk.Physical examinationrevealedmild muscle tremors, stiffness of hindlimbs,ataxia, dry muzzle, and elevated temperature. Laboratory investigation revealed phosphorus, pot(Radostits, Gay et al. 2006)assium, and decreased Calcium.Based on the history, clinical signs and laboratory findings, the case was diagnosed as hypocalcaemia. With 400 ml of Inj. 25% Calcium Borogluconate I/V and supportive therapies, the animal responded positively to treatment and showed good recovery.